Correction: Accuracy improvement on quantitative analysis of the total iron content in branded iron ores by laser-induced breakdown spectroscopy combined with the double back propagation artificial neural network. Issue 11 (2nd March 2022) - Su, Piao; Liu, Shu; Min, Hong; An, Yarui; Yan, Chenglin; Li, Chen
Abstract : Correction for 'Accuracy improvement on quantitative analysis of the total iron content in branded iron ores by laser-induced breakdown spectroscopy combined with the double back propagation artificial neural network' by Piao Su et al., Anal. Methods, 2022, 14, 427–437, DOI: ; 10.1039/D1AY01881G .